Photometric variability of the 1H1936+541 star in 2008-2014 - Simon, A.O.; Vasylenko, V.V.; Metlova, N.V. (Advances in Astronomy and Space Physics, 2014)
We report the results of observations of the Be/X-ray binary system 1H1936+541. All of the data were obtained on the base of Lisnyky observational station (Astronomical Observatory of the Taras Shevchenko National University of Kyiv) and Southern Station of the Sternberg Astronomical Institute (Lomonosov Moscow State University), giving us three different CCDs in U, B, V, R, and I filters, from 2008 till 2014. During this time, photometrical variability occurred in all bands, however the most significant changes were present in U and I bands. Variabilities in these bands anti-correlate with each other and are in a good agreement with the model of decretion disks around Be stars. Thus, photometric variability claims for changes in the decretion disc structure. Further photometric and spectral observations can help us develop a physical model of this system.